Cellulose nanocrystals (CNCs) with different crystalline allomorph for oil in water Pickering emulsions. (1st March 2018) - Li, Xia; Li, Jun; Gong, Jie; Kuang, Yishan; Mo, Lihuan; Song, Tao
Highlights: CNCs-I and CNCs-II showed different crystal structure and morphologies. CNCs-II had higher hydrophilicity resulted in less stable emulsion than CNCs-I. Crystalline allomorph of CNCs plays main role to stabilization of Pickering emulsion. Abstract: In recent years, nanocelluloses have attracted a lot of interests as promising stabilizers for Pickering emulsion particularly in food, cosmetics and pharmaceutics industries. In this work, two cellulose nanocrystals (named CNCs-I and CNCs-II) with different crystalline allomorph were investigated as stabilizers for oil-water Pickering emulsion. CNCs were prepared by sulfuric acid hydrolysis of unmodified and mercerized microcrystalline cellulose (MCC), respectively. CNCs-I was needle-like particles (length – 200 nm, width – 16.4 nm), while CNCs-II was individual granules (length – 18.8 nm, width – 10.9 nm) with ellipsoid shapes. Both CNCs had surface charge density higher than 0.1 e/nm 2 . Pickering emulsions stabilized by CNCs-I had larger emulsion ratio, two times smaller droplet size and superior performance of stability than CNCs-II. It is concluded that crystalline allomorph of CNCs played more dominating roles to the stabilization of Pickering emulsion than morphologies of CNCs themselves in this work, and CNCs-II is not the good candidates as stabilizer for Pickering emulsion compared to CNCs-I.